What is behind the dualist and monist debate in International law? - Ganić, Senad (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
Discussion on the relationship between internal and international law takes a very long time and is still ongoing. Over time, this discussion is shaped into two theoretical understanding and explanation of this relations, which manifested in the legal science through the dualist and monist debate. Despite the fact, that the basics of these two theories are known to us, it seems that the additional dealing with the arguments that have been offered in this debate are very important. Especially because we believe, that one of these two theories, and this is the one that represents the dualistic approach, does not have its foundation only in law. On the contrary, it seems that the arguments of dualist theory, offers only attempts to seemingly under the guise of legal arguments, justify the concept of understanding of international law, which actually means its negation. Especially, if the basics of dualism are placed in relation with the contemporary international law and the modern conception of state sovereignty. Therefore, we believe that further review of this issue can be useful. Because the extending the effects of the norms of international law, which is the process that follows the development of this branch of law, this debate becomes actualiyed over and over again.